ANALISIS PERMINTAAN BERAS DI SUMATERA UTARA - Hasyrul Aziz Harahap (Quantitative Economics Journal, 2012)
Indonesia is often categorized as low food resilient nation, in the sense vulnerable to social unrest and rising global food prices. Where every year the number of requests or local domestic rice continue to increase along with the increasing number of people. This study aims to look at and determine how much influence the price of rice, corn prices and the number of population and GDP of the demand for rice in North Sumatra. Used in measuring and analyzing time series data (time series) and the cross-point (cross section) of the 25 districts / municipalities in the period from 2005 to 2010. Data analysis using fixed effects (fixed effect). The results showed a significant effect between the price of rice, the population and GDP of the demand for rice in North Sumatra. While corn prices do not influence of the demand for rice in North Sumatra. The magnitude of the effect is shown by the coefficient of independent variables, namely: -5.215489 for the variable price of rice, 13.08473 for the population, 4.736669 for the variable GDP.